Spesies Burung pada Beberapa Tipe Habitat di Kecamatan Lhoknga Kabupaten Aceh Besar - Samsul Kamal; Elita Agustina; Zahratur Rahmi (Universitas Islam Negeri Ar-Raniry, 2016)
Lhoknga subdistrict is an area that has a habitat for many species of fauna, including birds. References about species of birds in some habitats are still very limited. Therefore, it is necessary to make a research on bird species in several types of habitat in the district of Lhoknga. The aim of the research is to figure out birds species in several types of habitats in the Lhoknga subdistrict. The data were collected by using the point count method and line transects. The results showed that there were 39 species of birds from 21 families found in Lhoknga district. Based on the PP. No. 07 of 1999, it was found that there were 14 species of protected birds in Lhoknga subdistrict.